The effect of enzymatic treatments of pulps on fiber and paper properties - Žnidaršič-Plazl, Polona (Array, 2009)
Summary: Biotechnological treatment of pulps provides great potential for the reduction of energy consumption and greenhouse gas emissions. In the present work, the influence of different commercial cellulases and xylanases or their mixtures on the quality of different bleached kraft pulps was investigated. The effects of enzymes on reducing sugars release and changes in fiber length were assessed for 3 different eucalyptus pulps, for a pulp consisting of a mixture of hardwoods and for softwood pulp. Despite the extremely high enzyme concentrations used in this part of the study, almost no change in fiber length was observed for pulps treated with enzyme preparations alone, while all combinations of cellulases and xylanases resulted in significant changes in average fiber length, portion of fines and reducing sugars release. Besides, vessel cell deformation was observed as a consequence of all enzymes applications. Furthermore, physical and mechanical properties of laboratory sheets made with enzymatically treated pulps were evaluated for various refining conditions and compared to those of untreated pulps. Potential energy savings up to 17 % were achieved with enzyme treatment, but some decrease in pulp quality was also observed